Novel photoinitiators for 3D printing applications - Goh, Odelia (Nanyang Technological University, 2023)
Photoinitiators are a key component in photocurable resins, influencing the polymerisation rate, properties and performance of the 3D product formed. In biomedical 3D printing applications, photoinitiators are often required to be biocompatible, non-cytotoxic and water-soluble, with a suitable absorption wavelength. Yet, most commercially available photoinitiators are still lacking, with commonly used initiators found to exhibit either cytotoxicity effects or low solubility. Recent studies have showed potential for diazirines to be used as a biocompatible photoinitiator alternative. In this study, carboxyl, hydroxyl and ethylene glycol functionalized aryl diazirines were evaluated for their ability to initiate photopolymerisation in both neat and aqueous free-radical systems, at ultraviolet (365nm) and visible (405nm) wavelengths. 1% (mol/mol) of diazirines was used for each formulation. Photo-rheometry tests and photo-differential scanning calorimetry (Photo-DSC) were used to measure the steady-shear viscosity, dynamic mechanical properties and curing efficiency of the diazirines. It was found that all three diazirines were able to initiate the polymerisation of neat poly(ethylene glycol) diacrylate (PEGDA) at both 365nm and 405nm, forming a thin solid film after irradiation. Furthermore, all the diazirines demonstrated the ability to initiate polymerisation in aqueous environments. Overall, these results are promising and demonstrate the feasibility of using diazirines as photoinitiators in acrylate-based systems for hydrogels and biomedical applications.